Calculating real surface area of land parcels in hilly and mountainous regions - Tran Quoc, Binh; Xuan, Pham Thanh; Tuan, Pham Le; Thuy, Le Phuong; Linh, Nguyen Xuan; Huy, Man Quang (VNU Journal of Science: Earth and Environmental Sciences, 2017)
Currently, the legal area of a land parcel in cadastral map is defined as the projected area of the parcel on a map plane. However, in practice, the real surface area of parcels plays important role for land use. In plain regions, the differences between real and legal areas of parcels are negligible, but in hilly and mountainous regions, these differences are significant and must be accounted in land management. In this paper, the authors proposed a method for calculating real surface area of land parcels using GIS and data extracted from digital elevation models. The method was verified against Vietnam’s standard on cadastral map by using a simulated land parcel that is a part of a sphere, and got positive results. The method is then applied for calculating surface area of more than 2000 land parcels in Tien Xuan commune, Thach That district, Hanoi city. The obtained results showed that the differences between real and legal areas of land parcels can be up to 23% for forestry land at mountain side with a slope of above 30 o . In whole Tien Xuan commune, these differences have an average value of 2.4%. Keywords Land parcels, Cadastral Map, Topography, GIS References [1] Jenness J.S., Calculating landscape surface area from digital elevation models, Wildlife Society Bulletin, 32(3), 829-839, 2004. [2] Zhang Y., Zhang L., Yang C. et al., Surface area processing in GIS for different mountain regions, Forestry Studies in China, 13(4), 311–314, 2011. [3] Xue S., Dang Y., Liu J. et al, Surface area calculation for DEM-based terrain model, Survey Review 48(351), 1-8, 2016. [4] Larson R., Edwards B.H., Calculus, 10th Edition, Cengage Learning, 2013. [5] Bộ Tài nguyên và Môi trường. Thông tư số 25/2014/TT-BTNMT ngày 19/5/2014 quy định về bản đồ địa chính, Hà Nội, 2014.